Respuesta :

ANSWER
[tex]x = - \frac{5}{3} [/tex]

or

[tex]x = - \frac{9}{4} [/tex]

EXPLANATION

We want to solve the equation,

[tex]6 {(2x + 4)}^{2} = (2x + 4) + 2[/tex]

One interesting way to solve this equation is to equate everything to zero and solve as quadratic equation by factoring.

[tex]6 {(2x + 4)}^{2} - (2x + 4) - 2 = 0[/tex]

The above is a quadratic equation in
[tex](2x + 4)[/tex]

where

[tex]a=6,b=1,c=-2[/tex]

and
[tex]a \times c = - 2 \times 6 = - 12[/tex]

We use the factors,
[tex]-4,3[/tex]
to split the middle term to get,

[tex]6 {(2x + 4)}^{2} + 3 (2x + 4) - 4(2x + 4) - 2 = 0[/tex]

We factor to obtain,

[tex]3 (2x + 4)[2(2x + 4) + 1] - 2 [ 2 (2x + 4) + 1]= 0[/tex]

We factor further to obtain,

[tex](3(2x + 4) - 2)(2(2x + 4) + 1) = 0[/tex]

[tex](6x + 12 - 2)(4x + 8 + 1) = 0[/tex]

[tex](6x + 10)(4x + 9) = 0[/tex]

[tex]x = - \frac{10}{6} = - \frac{5}{3} [/tex]

or

[tex]x = - \frac{9}{4} [/tex]

The solution of the equation [tex]6{\left( {2x + 4} \right)^2} = \left( {2x + 4} \right) + 2[/tex] is [tex]\boxed{x=- \frac{5}{3}}{\text{ and }}\boxed{x =- \frac{9}{4}}.[/tex]

Further explanation:

The Fundamental Theorem of Algebra states that the polynomial has n roots if the degree of the polynomial is [tex]n[/tex].

[tex]f\left( x \right) = a{x^n} + b{x^{n - 1}} +\ldots+ cx + d[/tex]

The polynomial function has n roots or zeroes.

Given:

The equation is [tex]6{\left( {2x + 4} \right)^2} = \left( {2x + 4} \right) + 2.[/tex]

Explanation:

The equation [tex]6{\left( {2x + 4} \right)^2} = \left( {2x + 4} \right) + 2[/tex] is a quadratic equation and has 2 solutions or zeros.

Solve the equation [tex]6{\left( {2x + 4} \right)^2} = \left( {2x + 4} \right) + 2.[/tex]

[tex]\begin{aligned}6{\left( {2x + 4} \right)^2} &= \left( {2x + 4} \right) + 2\\6{\left( {2x + 4} \right)^2} - \left( {2x + 4} \right) - 2 &= 0\\\end{aligned}[/tex]

Further solve the above equation using middle term splitting.

[tex]\begin{aligned}6{\left( {2x + 4} \right)^2} - \left( {2x + 4} \right) - 2 &= 0 \hfill\\6{\left( {2x + 4} \right)^2} - 4\left( {2x + 4} \right) + 3\left( {2x + 4} \right) - 2 &= 0 \hfill\\3\left( {2x + 4} \right)\left[ {2\left( {2x + 4} \right) + 1} \right] - 2\left[ {2\left( {2x + 4} \right) + 1} \right] &= 0 \hfill\\\left[ {2\left( {2x + 4} \right) + 1} \right]\left[ {3\left( {2x + 4} \right) - 2} \right] &= 0 \hfill\\\end{aligned}[/tex]

Again solve the above equation.

[tex]\begin{aligned}\left( {4x + 8 + 1} \right)\left( {6x + 12 - 2} \right) &= 0\\\left( {4x + 9} \right)\left( {6x + 10} \right) &= 0\\4x + 9 &= 0\,\,\,\,\,\,\,\,\,\,or\,\,\,\,\,\,\,\,\,6x + 10 = 0 \\ 4x - 9&=0\,\,\,\,\,\,\,or\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,6x = - 10\\x &= \frac{{ - 9}}{4}\,\,\,\,\,\,\,or\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,x = \frac{{ - 10}}{6} \\\end{aligned}[/tex]

The solution of the equation [tex]6{\left( {2x + 4}\right)^2} = \left( {2x + 4}\right) + 2[/tex] is [tex]\boxed{x= - \frac{5}{3}}{\text{ and }}\boxed{x = - \frac{9}{4}}.[/tex]

Learn more:

1. Learn more about inverse of the functionhttps://brainly.com/question/1632445.

2. Learn more about equation of circle brainly.com/question/1506955.

3. Learn more about range and domain of the function https://brainly.com/question/3412497

Answer details:

Grade: High School

Subject: Mathematics

Chapter: Quadratic equation

Keywords: roots, linear equation, quadratic equation, zeros, function, polynomial, solution, cubic function, degree of the function.

ACCESS MORE